2012
DOI: 10.1161/strokeaha.111.634980
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Dispatcher Identification Algorithm for Stroke Emergencies

Abstract: Background and Purpose-Recent innovations such as CT installation in ambulances may lead to earlier start of stroke-specific treatments. However, such technically complex mobile facilities require effective methods of correctly identifying patients before deployment. We aimed to develop and validate a new dispatcher identification algorithm for stroke emergencies. Methods-Dispatcher identification algorithm for stroke emergencies was informed by systematic qualitative analysis of the content of emergency calls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 18 publications
2
59
1
4
Order By: Relevance
“…15,28 During calls to the EMSs for suspected stroke, speech problems have been the most frequently reported symptoms. 30 Similar to the findings of this phase, it has also been reported that speech problems were associated with a correct ambulance diagnosis of stroke. 20 Speech problems also affect the speed of response by the public: a rapid call (within 1 hour) to the EMSs was found to be more likely when speech problems were present.…”
Section: Discussionsupporting
confidence: 81%
“…15,28 During calls to the EMSs for suspected stroke, speech problems have been the most frequently reported symptoms. 30 Similar to the findings of this phase, it has also been reported that speech problems were associated with a correct ambulance diagnosis of stroke. 20 Speech problems also affect the speed of response by the public: a rapid call (within 1 hour) to the EMSs was found to be more likely when speech problems were present.…”
Section: Discussionsupporting
confidence: 81%
“…de 3,8%, obtenida en este estudio es muy baja; no fue posible cuantificar de forma prospectiva los factores de exclusión. En un estudio canadiense en 24.191 pacientes con isquemia cerebral 11,8% fue trombolisado, siendo el incumplimiento de la ventana terapeútica la principal causa de exclusión de trombolisis [27][28][29] .…”
Section: Discussionunclassified
“…STEMO has been integrated in public emergency medical services (EMS) provided by the Berlin Fire Brigade. For the identification of eligible patients with suspected stroke during the emergency call, a special interview algorithm was developed and integrated at the dispatcher level 10 . …”
Section: Introductionmentioning
confidence: 99%